Significance of the local anthropogenic effects in the dynamics of wild geese wintering on the Ramsar Site Lakes by Tata (Wetland City Tata) - Musicz, László; Faragó, Sándor (Ornis hungarica, 2021)
The Old Lake of Tata, an important wild goose roosting site in Central Europe, is unique in its location being in the middle of a city with a population of 24,000. Consequently, the site is subject to intensive human disturbances. Goose migration and wintering on the lake was studied for over 37 years (1984–2021). In addition to weather, hydrological, and feeding conditions, particular attention was focused on human influences (which were deemed generally disruptive, but also beneficial in some cases) that can induce significant changes in the population dynamics of the 30,000–50,000 wild geese from 13 species wintering here. Almost without exception, the largest observed changes in the abundance of wild geese roosting overnight on the Old Lake are due to anthropogenic effects. In the majority of cases, the most significant population changes are due to impacts associated with the operation and upkeep of the lake and the New Year’s Eve fireworks. As a result, the winter operation of the Old Lake has been regulated by the Wild Goose Preference Mode since 2011, and the City of Tata has banned the use of fireworks during the winter period since 2018. Consequently, the conditions for wild goose migration have improved significantly. However, the situation of the Old Lake is still quite fragile and more conservation measures are needed to protect it further.